Queer Appetites: Embodied Desire in Monica Meneghetti’s What the Mouth Wants - Beneventi, Domenico A. (Italian Canadiana, 2020)
Drawing upon José Esteban Mufioz’s notion of queer futurity, this article examines the links between memory, food, and sexuality in Monica Meneghetti’s What the Mouth Wants: A Memoir of Food, Love and Belonging. The memoir depicts how embodiment and affect are imprinted in memory and recirculated through narratives of familial loss and queer awakenings. It is through physical and emotional nourishment in every sense of the word that the protagonist remembers a past that is both troubling and seductive, and looks toward a future that is both queer and utopic. I suggest that the author’s queer identity as a bisexual and polyamorous woman is expressed through the sensations of the flesh and through the affects that shape the world around her, and shaped by one eye toward an untenable queer past and one toward a queer utopic future.